Sulfur-autotrophic treatment of Sb(V)-contaminated water across concentration levels: Toward effective antimony pollution control - Yahui Shi; Zhixiang Zhang; Heyu Wan; Lin Ma; Heng Chen; Ying Li; Jiahui Dai; Dongjin Wan (Process Safety and Environmental Protection, 2026)

DiTing v2.0: A Snakemake-Optimized Workflow for Multi-Omics-Based Biogeochemical Pathway Analysis - Xing Chen; Heyu Lin; Chunxu Xue; Yi Liu; Jiwen Liu; Min Yu; Xiaolei Wang; Xiaohua Zhang (Journal of Ocean University of China, 2026)

Correction: Metagenomics reveals diverse community of putative mercury methylators across different biogeochemical niches in Sansha Yongle blue hole - Heyu Lin; Xiao-Yu Zhu; Chun-Xu Xue; Peng Yao; Liang Fu; Zuosheng Yang; Xiao-Hua Zhang; John W. Moreau (Marine Life Science & Technology, 2026)

Metagenomics reveals diverse community of putative mercury methylators across different biogeochemical niches in Sansha Yongle blue hole - Heyu Lin; Xiao-Yu Zhu; Chun-Xu Xue; Peng Yao; Liang Fu; Zuosheng Yang; Xiao-Hua Zhang; John W. Moreau (Marine Life Science & Technology, 2025)
Methylmercury (MeHg) is a potent neurotoxin and bioaccumulates in food webs. Microbial transformation of inorganic mercury (Hg) produces most of the MeHg in the marine environment. The gene pair hgcAB encodes for Hg methylation, a process predominantly attributed to anaerobic bacteria. However, recent studies indicate the formation of methylmercury in low-oxygen zones within marine water columns, although the mechanisms remain poorly understood. “Blue holes” are marine sinkholes containing redox gradients stratified with depth and high microbial diversity across a range of biogeochemical cycles. Here, we present the first metagenomic analysis focused on the potential for Hg methylation in a blue hole ecosystem. Yongle Blue Hole (YBH), currently the world’s deepest known blue hole, was selected as a representative site to investigate the genetic potential for Hg methylation and to explore the functional capabilities of putative Hg-methylators within this unique environment. Metagenomic analysis showed that the anoxic sulfidic deep water was likely to be a hotspot for Hg methylation, driven by abundant and diverse Deltaproteobacteria. In the suboxic intermediate layer, Nitrospina and Myxococcota dominated the Hg-methylating community. Furthermore, Hg methylators were found to have different lifestyles (free-living or particle-associated) and to occupy distinct ecological niches within the YBH. In addition, the contribution of sinking particles to Hg methylation, especially in the deep anoxic water column, was highlighted. Our study unveils the biodiversity and survival strategies of Hg methylators across distinct environments. The findings suggest that blue holes could serve as model stratified ecosystems for studying Hg methylation processes across different habitats.

Hydrogel-engineered platforms for efficient solar interfacial evaporation: Current status and future directions - Junnan Jiang; Heyu Jin; Yao Lu; Xiaohua Liu; Hongyu Ge; Lin Mu (Journal of Water Process Engineering, 2025)

Transcriptome analysis reveals important regulatory genes and pathways for tuber color variation in Pinellia ternata (Thunb.) Breit - Cong Yin; Ding Tang; Xiaoyu Liu; Zihan Li; Yulin Xiang; Kaiming Gao; Heyu Li; Lin Yuan; Bisheng Huang; Juan Li (Protoplasma, 2023)

Significance of Vibrio species in the marine organic carbon cycle—A review - Xiaohua Zhang; Heyu Lin; Xiaolei Wang; Brian Austin (Science China Earth Sciences, 2018)